The Framework of Socio Demographic Factors, Neighborhood Safety, and Physical Activity as Factors of Mental Health and Self-Rated Health - Shaista Imtiaz, Kiren Farooq, Sadia Abidi Malik, Attaullah Bangulzai, Muhammad Irfan, Muhammad Khalil, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Researchers looked at the processes behind how socioeconomic position affects mental health and self-reported health, as well as how those connections differed by racial group, age, and sex. Methods: Researchers looked at the responses of 46 934 persons who took part in the 2020 Health Survey. To evaluate the impacts of SES, neighborhood safety, in addition physical exercise on psychological health and SRH, we employed a route analysis. Result: Low SES were linked to increased neighborhood safety worries, that were being linked to lower physical activity, that remained subsequently linked to lower mental health and SRH. Although the model remained comparable across race and cultural classes, the average level in the components varied. Conclusion: SES has a significant impact on SRH and mental health, with race and sex adding to the complexity. It's crucial to understand psychological (neighborhood security) also behavioral (vigorous exercise) elements that impact mental health so that treatments and programmes may be tailored to promote general health.